Betsy and the Emperor - Rabin, Staton (New York : Margaret K. McElderry Books, 2004)
In 1815 on the remote island of Saint Helena, fourteen-year-old Betsy Balcombe develops a friendship with Napoleon Bonaparte who, after his defeat at Waterloo, is brought there as an exile and is housed with her family.
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- Juvenile fiction; Abell, Lucia Elizabeth Balcombe, -- -1871 -- Juvenile fiction; Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- Fiction; Abell, Lucia Elizabeth Balcombe, -- d. 1871 -- Fiction; Friendship -- Fiction; Saint Helena -- History -- 19th century -- Fiction